Philippines : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This article is an empirical analysis on tax collections in the Philippines. The tax system is characterized by a rule of tax incentives provided by 13 investment agencies. Tax collections showed regular growth. The GDP ratio increased from 12.1 percent (2009) to 12.8 percent (2012), but the revenue-to-GDP ratio was low to fill large gaps for education, health, and infrastructure; therefore the authorities encompassed the sin taxes (alcohol and tobacco excises). The most important source of income for the Philippines is the labor export. This large-scale labor emigration fetches a sufficient amount of annual inflows of more than 9 percent of GDP.